Role of fucoidan in stimulating osteoblast cells in alveolar bone loss: Peran fucoidan dalam menstimulasi sel osteoblas pada kasus kehilangan tulang alveolar - Nurlindah Hamrun; Alya Hilda Saifuddin; Alya Khaerunnisa I Day; Hemayu Aditung; Sri Handayani Saharuddin; Megatriani Matandung; Fadilla Ani Saputri; A. Agum Aripratma; A. Muh. Ferdian Alfarabi; Nadya Aura Amalia (Makassar Dental Journal PDGI Makassar, 2022)
Alveolar bone loss is a characteristic of the development of periodontitis; its prevention is a major clinical challenge in the treatment of periodontal disease. Alveolar bone loss can significantly affect a patient's quality of life. In addressing the chal-lenges of recovering alveolar bone loss, fucoidan has attracted attention as a potential material due to its numerous biological activities, one of which is its potential to regulate osteogenic cell function so as to facilitate osteoblast cell proliferation and promote bone mineralization and development. This literature discusses the role of fucoidan, especially in stimulating osteo-blast cells in cases of alveolar bone loss.